Sabotage America's enemies within the CIA - Scarborough, Rowan (Regnery Pub., 2007)
Using first-rate sources in all levels of national security--from field officers to high-ranking analysts to former intelligence heads--veteran journalist Scarborough reveals how CIA bureaucrats are undermining President Bush and the War on Terror through disinformation, incompetence, and outright sabotage.--From publisher description.